Organizational Culture And Ecotourism Resorts’ Performance: A Case Study At Lake Kenyir, Malaysia - Jamil, Mohd Fitri Che (2011)
The recent debates on ways to increase the performance of tourism have persisted the current study to explore the issue of organizational culture and performance of ecotourism resorts. There is a need for all tourism stakeholders to be aware of the nature of organizational culture that is available so they can focus on establishing performance-enhancing culture. This study aims to investigate the relationship between the organizational culture and the performance of resorts in an ecotourism area.